Extração de óleo de borra de café (Coffea arábica) por prensagem a frio vs. extração com solvente assistida e não assistida com ultrassom: rendimento dos processos e perfis de voláteis, sensorial, de ácidos graxos e antioxidante dos óleos obtidos - Lima, Lucas Almeida Leite Costa (2019)
In the world, the consumption of the coffee generates annually about 22 thousand tons of spent coffee ground that, after drying contain more than 10% of oil. The objective of the present research was to evaluate the advantages and disadvantages of the cold pressing extraction of the oil present in coffee residues (Coffea arabica) comparing to solvent extraction, with and without the use of ultrasound. Spent coffee ground generated by espresso machine was dried at 10% moisture, and the oil extracted by three methods: cold pressing (55 ton), and ethanol extraction at 30 ° C, assisted and not assisted with ultrasound. The solvent extraction conditions were optimized by varying the spent coffee ground / solvent ratio and the extraction time, using a DCCR design, Response Surface Methodology and Desirability function. The oils obtained were characterized for humidity, relative density and peroxide, refraction, acidity, saponification and iodine indexes, fatty acid profile and antioxidant capacity (DPPH, ABTS and ORAC). The volatiles present in the oils headspace were isolated by SPME (DVB / Carboxen / PDMS fiber), separated on an HP-5MS capillary column and identified in GC-MS system. The conditions of isolation were optimized by varying the adsorption temperature in the fiber and the extraction time, using a DCCR design, Response Surface Methodology and Desirability function. Trained judges generated the aroma profile of the oils using ADQ®; the results were analyzed by ANOVA, Tukey (p≤0.05) and ACP. On a dry basis, the lipid content of the spent coffee ground was ~ 13%. The cold pressing showed an average yield of 29%. The optimum solvent extraction conditions without the use of ultrasound occurred with 550 mL of solvent / 100 g of spent coffee ground and 36 minutes of extraction; and showed 77% yield. Ultrasound, extraction time to give 78% yield was 10 minutes. Oils extracted by cold pressing, with ultrasonic assisted solvent, and with solvent without the use of ultrasound presented relative density of 0.93; 0.95; 0.93 g.cm-3, refractive indexes of 1.4702; 1.4547; 1.4561, acidity 0.99; 1.30; 1.38 mg KOH.g-1, saponification of 196; 195; 195 mg KOH.g -1, iodine 89.5; 91.5; 91 gI.g.g -1, peroxides of 3.41; 2.31; 1.99 meq O2.kg-1, all values within the ranges established by the Codex Alimentarius Commission for edible oils. Linoleic acid (C18: 2) was the major fatty acid in oils, followed by palmitic acid. The oils extracted with solvent had higher antioxidant capacities (by ORAC and ABTS methods) and higher total phenolic compounds than the oil extracted by cold pressing. The optimal condition of volatile insolation occurred with exposure of the fiber at 63ºC for 60 minutes. Furans and pyrroles were the main chemical classes in the oil extracted by cold pressing, representing respectively 13% and 11% of the total area of the chromatogram. Hydrocarbons and alcohols were the major chemical class in the solvent extracted oils. The oil generated by cold pressing presented an higher aromatic note described as "coffee beverage" (p≤0.05) than the others, which besides presenting notes described as "roasted" and “grounded coffee”, presented peculiar aromas, described as "alcohol","pungent" and "sweet". The three extraction methods evaluated yielded nutritionally advantageous products, the oil obtained by cold pressing being more suitable for food applications, and the oils extracted with solvent, suitable for the elaboration of nutritional supplements, cosmetics and hygiene products.